TCH-001 A Case Report of a Woman Hospitalised For Severe Loss of Weight and Psychotic Decompensation After Taking a Slimming Preparation. (12th March 2013) - Layoun, N; Blanco, C; Benassaya, A; Rebiere, H; Civade, C
Abstract : Background: A French pharmacovigilance centre recorded the case of a 40-year-old woman hospitalised for severe loss of weight (16 kg in 3 months) associated with hypokalaemia, inflammatory syndrome and psychotic decompensation, after taking a slimming preparation. It was sold on the internet as an herbal medicine containing natural authorised substances. Purpose: The expertise of the French Health Agency (ANSM) was requested to find, identify and measure the active substances (ASs) contained in the product. Materials and Methods: At first, the analysis strategy was a general screening method to search for ASs in the product, performed with gas chromatography–mass spectrometry [GC-MS] and high performance liquid chromatography-mass spectrometry [HPLC-MS]. Then a specific method confirmed the identification and quantified the AS using ultra performance liquid chromatography-diode array detection [UPLC-DAD]. Results: The slimming preparation was presented in capsules containing a fine, brown homogeneous powder. Gas Chromatography revealed two main ASs and the mass spectrometry analysis identified them as sibutramine and phenolphthalein. The result of HPLC/MS also revealed two main ASs on chromatogram with molecular masses of 279 g.mol-1 and 318 g.mol-1. The UPLC-DAD, using the method 'search for and quantification of 34 ASs in a slimming formulation', confirmed these preliminary results and also gave a quantity of 8 mg of sibutramine and 20 mg of phenolphthalein per capsule. Conclusions: Sibutramine is the AS in Sibutral (10 and 15 mg), an anti-obesity medicine, withdrawn from the market in January 2010 because of increased cardiovascular risk and an unfavourable benefit-risk assessment. Because of its carcinogenic potential phenolphthalein (a laxative) has been forbidden in France since 1999. Sibutramine and phenolphthalein were probably responsible for the clinical symptomatology in this patient. These slimming products sold outside the pharmaceutical distribution network have not been approved by the authorities resulting in a health risk, including fatal outcomes. No conflict of interest.